Development of appreciation of traditional Chinese operas textbooks for undergraduate student teaching - Yan, Hua; Daoruang, Krisada (Edelweiss Applied Science and Technology, 2025)
This study aimed to explore the development of textbooks for undergraduate Chinese traditional opera appreciation courses and their supporting role in MOOC teaching. Through investigating the teaching problems and students’ needs in the drama course, a set of drama teaching materials suitable for the MOOC environment was researched and developed, and its effectiveness in practical teaching was evaluated. A combination of questionnaire surveys, expert interviews, and teaching experiments was used to investigate undergraduates and teachers from three universities in Zhejiang Province. The results show that the opera textbooks developed not only effectively enhance students’ interest and understanding of traditional Chinese opera but also provide effective support for the MOOC platform, enrich the teaching content and form, and promote students’ inheritance and identification of opera culture.